COVID-19: Lessons learned after a year of pandemic in Peru - Lizaraso Caparó, Frank (2021)
It is just over a year since the World Health Organization (WHO) was informed by the Chinese authorities of 27 cases of pneumonia of unknown etiology in the city of Wuhan. Thirty days later, the outbreak of a new coronavirus was declared a public health emergency of international concern, which in just one week had already recorded more than two tens of thousands of cases worldwide (99.2% in China and 0.8% in 24 other countries), so the WHO warned that the risk of spread would be very high in China and high throughout the rest of the world. Today we are faced with a figure that exceeds 93 million cases and more than 2 million deaths in the world. In Peru, more than one million cases and 38,000 deaths have been reported.